Response to Improving the Success Rate of Chest Compression-Only CPR by Untrained Bystanders in Adult Out-of-Hospital Cardiac Arrest: Maintaining Airway Patency May Be the Way Forward. (February 2018) - Nolan, Jerry P.; Perkins, Gavin D.; Neumar, Robert W.; Olasveengen, Theresa M.
Abstract : Published ahead of print December 11, 2017.